The role of innovative leadership in improving organizational performance and enhancing competitive advantage within educational institutions (The International Journal of Educational Sciences and Arts, 2026)
This study takes into account the Kingdom’s directions to develop and enhance the leadership aspect of its organizations so that they can achieve innovative leadership for excellence in organizational performance and enhance the competitive advantage of the educational institution to provide educational services in a manner appropriate to the Kingdom’s Vision 2030. The study aimed to: identify the reality of practicing innovative leadership among managers of educational institutions, Identify the level of organizational performance in educational institutions, and identify the level of competitive advantage in educational institutions and clarifying the obstacles to innovative leadership to improve organizational performance and enhance competition within educational institutions. The study used the descriptive analytical approach. This study used the descriptive approach that relies on qualitative analysis of available data. It falls within library documentary studies to clarify the role of innovative leadership in improving organizational performance and enhancing competitive advantage within educational institutions. By reviewing and benefiting from the previous theoretical heritage, the study concluded with a set of results, the most important of which are: Education within educational institutions at all levels conflicts with the role of innovative leadership in improving organizational performance and enhancing competitive advantage within educational institutions, due to the presence of several obstacles, including traditional training methods, evaluation methods based on memorization, and lack of educational capabilities -in addition to school curricula Education also needs diverse and advanced learning and teaching strategies in order for innovative leadership to help improve organizational performance and enhance competitive advantage within educational institutions by enriching their information and developing their skills and innovative abilities. This cannot be achieved without the presence of a competent teacher who gives his students opportunities for scientific thinking and pushes them to develop their mental and innovative abilities.
Keywords: Innovative Leadership; Organizational Performance; Competitive Advantage; Educational Institutions; Educational Management